Tidlig islamisk historie i mnemohistorisk betydning - et case-study af sûrat al-kâfi rûn - Butler, Jean (Religionsvidenskabeligt Tidsskrift, 2008)
The notion of the Other is basically about distinguishing between oneself and others. As such, it is a vital element in constructing an identity, be that identity socially, religiously or politically defined. This article takes its theoretical point of departure in German Egyptologist Jan Assmann's thesis on monotheism as building on a Mosaic Distinction between 'true' and 'false' in religion; 'belief' and 'unbelief,' and ultimately 'us' and 'them'. It focuses on some of the more grave aspects of Islamic monotheism, namely those of religiously defining oneself as the more righteous party in opposition to other people perceived as being unbelievers, or even shayâtîn, 'satans.' Furthermore, as also pointed out by Assmann, in salvation-oriented monotheistic religions 'forgetting' means being lost, while 'remembrance' spells salvation. This insight appears to be relevant for a study of the Islamic religious tradition in particular, constructed as this is on a strong historical tradition of transmission of memorized and normative narratives. Cultural Memory, in the shape of the narrative Qur'ân, staging and defining Islamic religious culture and telling its story of origins is thus here viewed as crucial to that culture's continued relevance and existence. The exemplary case-study is sûrat al-kâfi rûn, 'The Infidels;' at the same time illustrating the inherited Mosaic Distinction in Islam.